Gender minorities and persons with disabilities defining their perpetrators at music festivals - Kinnunen, Maarit; Honkanen, Antti (Informa UK Limited, 2025)
There are recent studies on sexual harassment at music festivals, particularly toward female attendees. However, studies on perpetrators of minority members are scarce. We wanted to discover the prevalence of inappropriate behavior toward gender minorities and persons with disabilities and give voice to their experiences, aiming to identify ways to improve inclusivity at music festivals. The research data comprised survey responses (n = 16,681) and nine in-depth interviews of minority members and their Personal Assistants. Statistical methods and Interpretative Phenomenological Analysis were employed for the research. Both gender minorities and persons with disabilities faced more inappropriate behavior than other festival attendees, and these experiences increased if the person belonged to both minorities. The perpetrators were divided into four groups: those with positive attitudes but incorrect actions; those who were ignorant or did not care; those who had negative, prejudiced behavior, and those who were aggressive and expressed hate. Organizers should take various actions to increase inclusivity in their festivals: defining safer space policies; training, programming and recruitment; hiring a harassment contact team; improving the control of alcohol consumption, and introducing a sensory-friendly space.